Persepsi Peserta Diklat tentang Kompetensi Kepribadian Widyaiswara pada Diklat Teknis Pemetaan Konflik Tenurial - Urfi Izzati; Ultah Dianawati (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
Personality competence is one of competencies that must be possessed by widyaiswara. As a role model in the learning process, widyaiswara must have good personality. Nowadays, research on widyaiswara’s personality competencies is few in number, even though this competency is important to know to improve widyaiswara’s performance in improving the quality of learning. This study aims to determine the training participants’ perceptions of widyaiswara’s personal competence in the technical training on Tenure Conflict Mapping at the BDLHK Kadipaten. The study used quantitative method and was conducted in February 2019. The population of the study is all training participant (30 participant). Data collecting used questionnaire whose results were analyzed descriptively. The results showed that the technical training of widyaiswara on Tenure Conflict Mapping had steady, stable, and mature personality of 88.33% with very good category, wise and authoritative personality of 86.53% with very good category, personalities that became role models of 86.88% with very good category, and noble character of 89.58% with very good category. The result showed that widyaiswara have very good personal competencies, so hopefully widyaiswara can maintain the achievement and need to improve the ability to create a pleasant learning atmosphere, the ability to master classes and materials, responsiveness to renewal and openness to new innovations in both material, media, and methods, politeness of speaking style, and timeliness. In addition, widyaiswara also have to improvelearning management competencies, social competency, and substantive competency to improve widyaiswara’s performance in order to improve quality eduction and training.